Analysis of Small Business and Cooperative’s Growth in Tourism Areas Integrated with Nurmilad Boarding School at Lempong, Wajo Regency, South Sulawesi - Bisma Widyawan; Vikky Berliana Prasanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This research is entitled Analysis of Small Business and Cooperative’s Growth in Tourism Area Integrated with Nurmilad Islamic Boarding School (NBS), Lempong, Wajo Regency, South Sulawesi. The purpose of this research is to find out and analyze the growth, constraints, and efforts in overcoming the obstacles that occur for small businesses and cooperative in tourism area integrated with Nurmilad Boarding Islamic Boarding School. This research used descriptive qualitative analysis method where data collection obtains by observation and interviews involving six informants.Based on the descriptive and analysis results, it can be concluded that the growth of small businesses and cooperatives in the sharia tourism area integrated with the Nurmilad Boarding School is very significant. The growth of the sharia tourism area has an impact on the growth of small businesses and cooperatives because of the integration policy between the tourist area management and the Nurmilad Islamic Boarding School. The obstacles found were the lack of human resources, inadequate accessibility of infrastructure, lack of maximum promotion, and the mindset of the people who were still influeced with agrarian mindset. Therefore, the efforts made are to collaborate with local governments to improve road infrastructure, maximize promotions so that more visitors come, and always analyzing consumer needs.